Non-Stationary von Neumann Model whit Limit Technology - Panek, Emil (Studia Oeconomica Posnaniensia, 2013)
The vast majority of papers on the turnpike theory consider a stationary economy with constant technology (over time). There are only few attempts to go beyond the "vicious circle" of stationarity and to trace the so called turnpike effect in a non-stationary Neumann-Gale economy with unstable technology. This article undertakes this task. In the paper "weak" and "very strong" versions of the turnpike theorem in a non-stationary von Neumann economy are presented, with the technology converging to a certain technology limit.